Annular pancreas in adults: single unit experience from a tertiary care centre of Northern India - Gupta, Amit; Kumar, Utkarsh; Jain, Jaydeep; Kundal, Ashikesh; ., Natasha; Rajput, Deepak; Kumar, Navin; Chauhan, Udit (International Journal of Research in Medical Sciences, 2020)
Annular pancreas is a rare congenital anomaly which usually presents with gastrointestinal symptoms early in life. In adults mostly it remains asymptomatic or may present with abdominal or features of duodenal obstruction the increased diagnosis of which is attributed to the improved imaging modalities. We hereby report our experience of adult annular pancreas in whom clinical presentation initially mimicked gastric or duodenal outlet obstruction. Adult annular pancreas was diagnosed with the aid of computed tomography of the abdomen and treated successfully with Roux-en-Y isoperistaltic gastrojejunostomy.